A hydrotrope pretreatment for stabilized lignin extraction and high titer ethanol production - Hairui Ji; Le Wang; Furong Tao; Zhipeng Yao; Xuezhi Li; Cuihua Dong; Zhiqiang Pang (Bioresources and Bioprocessing, 2022)
Abstract The biomass pretreatment strategies using organic acids facilitate lignin removal and enhance the enzymatic digestion of cellulose. However, lignin always suffers a severe and irreversible condensation. The newly generated C–C bonds dramatically affect its further upgrading. In this study, we used a recyclable hydrotrope (p-Toluenessulfonic acid, p-TsOH) to dissolve lignin under mild condition and stabilized lignin with a quenching agent (formaldehyde, FA) during extraction, achieving both value-added lignin extraction and efficient enzymatic saccharification of cellulose. Approximately 63.7% of lignin was dissolved by 80% (wt. %) p-TsOH with 1.5% FA addition at 80 °C, 30 min. The obtained lignin was characterized by FTIR spectroscopy, TGA, 2D HSQC NMR spectroscopy, and GPC. The results indicated that the extracted lignin exhibited excellent properties, such as light color, a low molecular weight (Mw, 5371 g/mol), and a narrow polydispersity (M w/M n, 1.63). The pretreated substrate was converted to ethanol via a quasi-simultaneous saccharification and fermentation process (Q-SSF). After fermentation of 60 h, the ethanol concentration reached 38.7 ± 3.3 g/L which was equivalent to a theoretical ethanol yield of 82.9 ± 2.2% based on the glucan content, while the residual glucose concentration was only 4.69 ± 1.4 g/L. In short, this pretreatment strategy protected lignin to form new C–C linkages and improved the enzymatic saccharification of glucan for high-titer ethanol production. Graphical Abstract